Where are you going? Marketing mix analysis of a tourim destination in Santa Catarina state (Brazil) - Giancarlos Francisco Miguel (Revista Brasileira de Pesquisa em Turismo, 2008)
This paper presents a research carried out in order to analyze the “four P” of the marketing mix (product, price, place and promotion) in a seaside tourism destination in Santa Catarina, through the eyes of some interviewees representing each public and private business sector. It was a qualitative research, exploratory and descriptive, and the data were obtained through semi strutured interviews. The outcome revealed that the destination is not structured yet to be considered a touristic product, because at present it is changing from sun and sea tourism to nature tourism and it lacks investments for infra structure, mainly in sewage and roads. Price was considered fair by entrepreneurs and extremely high by civil servants. Commonly the destination is placed directly in the market, with no intermediation of tour operators or retail agents. and it is promoted through tourism fairs, newspapers and journals as well as internet. Actions are generally not planned, no partnerships between trade and public sector were detected nor integration with other components of the marketing mix.